Analysis of the Maturity of Financial Information Systems in Regional Public Service Agencies of the Special Region of Jakarta Province - Affandi, Ichsan; Salomo, Roy V (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2025)
The modernization of financial information systems within local governments is a key factor in strengthening transparency, accountability, and the overall quality of public service delivery. This research examines the maturity level of Financial Information Systems implemented in Regional Public Service Agencies (BLUD) in the Special Region of Jakarta Province by applying the DeLone and McLean Information System Success Model (DeLone & McLean, 2003)This research applied a post-positivist approach by combining document analysis with in depth interviews involving key informants, namely BLUD personnel, SKPD officials responsible for BLUD supervision, and information system developers. The evaluation focused on four dimensions: system reliability and accuracy, integration, accessibility, and user capacity. The findings reveal that all dimensions experience various constraints, with integration and system reliability and accuracy identified as the most critical weaknesses. The limited level of integration is primarily attributable to the absence of effective linkage between the BLUD information system and the Regional Government Information System (SIPD), which leads to duplicated data entry and delays in the consolidation of financial information. At the same time, shortcomings in system reliability and accuracy are reflected in the high frequency of financial report revisions. In response to these issues, the study recommends the establishment of an integrated BLUD financial information system that is directly connected to SIPD, along with improvements to the mechanisms for correcting and validating financial reports.